Intelligent parking system using machine learning - Abrar, Md. Ishtiak; Saha, Shawon; Halim, Hamim Shabbir; Shafi, Shoaib Ahamed (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.